Development of a methodology taking into account the temperature dependence of material properties in simulation of wear in fast-rotating pivot jewel bearing support - D. N. Zhuravlyov; A. I. Borovkov (Омский научный вестник)
The pivot jewel bearing is an important node of some classes of industrial equipment; at nominal operating modes, the speed of relative rotation of the contact surfaces can reach 103 revolutions per second, while the operating time can be measured in years; under such conditions, it is necessary to take into account the wear of the contact surfaces; in this paper, a technique for modeling the dry friction wear of a fast-rotating support pair is proposed, taking into account changes in the properties of materials due to surface heating, based on solving the wear contact problem in a stationary formulation using Archard’s law; the effect of taking into account the temperature dependence of material properties in wear modeling process is demonstrated.